Suppressive Effect of 4-Hydroxy-2-(4-Hydroxyphenethyl) Isoindoline-1,3-Dione on Ovalbumin-Induced Allergic Asthma - Huang, Jin; Su, Mingzhi; Lee, Bo-Kyung; Kim, Mee-Jeong; Jung, Jee H.; Im, Dong-Soon (Biomolecules & therapeutics, 2018)
4-Hydroxy-2-(4-hydroxyphenethyl)isoindoline-1,3-dione (PD1) is a synthetic phthalimide derivative of a marine compound. PD1 has peroxisome proliferator-activated receptor (PPAR) γ agonistic and anti-inflammatory effects. This study aimed to investigate the effect of PD1 on allergic asthma using rat basophilic leukemia (RBL)-2H3 mast cells and an ovalbumin (OVA)-induced asthma mouse model. , PD1 suppressed β-hexosaminidase activity in RBL-2H3 cells. In the OVA-induced allergic asthma mouse model, increased inflammatory cells and elevated Th2 and Th1 cytokine levels were observed in bronchoalveolar lavage fluid (BALF) and lung tissue. PD1 administration decreased the numbers of inflammatory cells, especially eosinophils, and reduced the mRNA and protein levels of the Th2 cytokines including interleukin (IL)-4 and IL-13, in BALF and lung tissue. The severity of inflammation and mucin secretion in the lungs of PD1-treated mice was also less. These findings indicate that PD1 could be a potential compound for anti-allergic therapy.